(untitled) (Plant Tissue Culture and Biotechnology, 2015)
An in vitro regeneration and Agrobacterium?mediated genetic transformation protocol was optimized for a local tomato variety, BARI Tomato?8 using cotyledonary leaf and hypocotyls explants. The explants were treated with various growth regulators in MS at different concentrations and combinations. Highest number of multiple shoot induction was observed from both the explants cultured in MS supplemented with 8.88 ?M BAP and 0.57 ?M IAA. Half strength of MS supplemented with 1.14 ?M IAA was found to be the best for root induction from excised shoots. Agrobacterium mediated genetic transformation was carried using pBI121 plasmid harboring ??glucuronidase (GUS) reporter and nptII selectable marker genes. Transient GUS assay confirmed that both the explants pre?cultured for two days showed best transformation efficiency in bacterial suspension having optical density (OD) of 0.8 (at 600 nm) for 15 min and co?cultivation period of 3 days. The shoots regenerated from transformed cotyledonary leaf explants survived at 200 mg/l kanamycin selection. The presence of expected amplicon corresponding to the GUS gene was confirmed by PCR. This protocol paves a way for developing disease resistant tomato variety using target gene/s. Plant Tissue Cult. & Biotech. 25(1): 87-97, 2015 (June)